Staphylococcus aureus Nasal Carriage and Autoimmune Diseases: From Pathogenic Mechanisms to Disease Susceptibility and Phenotype - Ceccarelli, Fulvia; Perricone, Carlo; Olivieri, Giulio; Cipriano, Enrica; Spinelli, Francesca; Valesini, Guido; Conti, Fabrizio (International journal of molecular sciences, 2019)
The role of infective agents in autoimmune diseases (ADs) development has been historically investigated, but in the last years has been strongly reconsidered due to the interest in the link between the microbiome and ADs. Together with the gut, the skin microbiome is characterized by the presence of several microorganisms, potentially influencing innate and adaptive immune response. S. aureus is one of the most important components of the skin microbiome that can colonize anterior nares without clinical manifestations. Data from the literature demonstrates a significantly higher prevalence of nasal colonization in ADs patients in comparison with healthy subjects, suggesting a possible role in terms of disease development and phenotypes. Thus, in the present narrative review we focused on the mechanisms by which S. aureus could influence the immune response and on its relationship with ADs, in particular granulomatosis with polyangiitis, rheumatoid arthritis, and systemic lupus erythematosus.